Comparison of the effectiveness of ARASAAC pictograms and commercially available pictograms in children with autism spectrum disorder and complex communication needs - Zurita Díaz, Antonio Javier; Couceiro Figueira, Ana Paula; Calleja Reina, Marina (Revista de Investigación en Logopedia, 2026)
Communication skills can be severely affected in Level 3 autism spectrum disorder (ASD), also impacting social interactions and behavior, which presents a significant challenge for school-aged children. In these cases, the use of augmentative and alternative communication (AAC) is highly recommended. However, the wide variety of available AAC resources makes selecting the most suitable option difficult. This study compares two pictographic systems: ARASAAC pictograms and commercially available pictograms, aiming to analyze their impact on participants’ progress. A quasi-experimental design was employed with 40 children with Level 3 ASD and complex communication needs: 21 used ARASAAC pictograms, while the remaining 19 used pictograms from Mi Estuche de Pictos. These pictograms were introduced through activities based on the aided augmented input strategy, pairing the speech therapist’s natural oral input with corresponding visual representations. After 45 intervention sessions and three evaluation points using the Vineland-3 Scale, children who used ARASAAC pictograms showed significantly greater improvements in receptive and expressive communication, social skills, and behavior. Although the results with Mi Estuche de Pictos were also positive, ARASAAC stood out due to its iconicity, accessibility, and customization capabilities—factors that contributed to more positive progress in children with Level 3 ASD over time.